Patient understanding of genetic information influences reproductive decision making in retinoblastoma. Issue 6 (17th August 2017) - Foster, A.; Boyes, L.; Burgess, L.; Carless, S.; Bowyer, V.; Jenkinson, H.; Parulekar, M.; Ainsworth, J.; Hungerford, J.; Onadim, Z.; Sagoo, M.; Rosser, E.; et al.
Abstract : Background: Retinoblastoma is the most common malignant tumour of the eye in childhood, with nearly all bilateral tumours and around 17% to 18% of unilateral tumours due to an oncogenic mutation in the RB1 gene in the germline. Genetic testing enables accurate risk assessment and optimal clinical management for the affected individual, siblings, and future offspring. Material and Methods: We carried out the first UK‐wide audit of understanding of genetic testing in individuals with retinoblastoma. A total of 292 individuals aged 16 to 45 years were included. Results: Patients with bilateral disease were significantly more likely to understand the implications of retinoblastoma for siblings and children. There was a significant association between not knowing the results of genetic testing or not understanding the implications and not having children, particularly in women. Surprisingly, this was also true for individuals treated for unilateral disease with a low risk of retinoblastoma for their offspring. Conclusion: We are concerned that individuals may be making life choices based on insufficient information regarding risks of retinoblastoma and reproductive options. We suggest that improvement in transition care is needed to enable individuals to make informed reproductive decisions and to ensure optimal care for children born at risk of retinoblastoma. Abstract : Respondents who understood the genetic implications of retinoblastoma were significantly more likely to have children than those who did not understand the genetic implications of retinoblastoma